Increasing the Knowledge of Mental Health of Young Adults through Video-Assisted Education: A Pilot Study in Surabaya - Safira Nur Izzah; Rakha Achmad Maulana; Dimas Setyanto; Ludy Diana Wiradhika; Annette d'Arqom (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Background: Young adults (<25 years old), a 49% proportion of the Indonesian population, is one crucial component that might determine the future of the nation and achieve Indonesia Emas or Golden Indonesia in 2045. Anxiety is one of the effects of the COVID-19 Pandemic, as one out of five Indonesian people could have suffered from anxiety, especially young adult women. This activity would like to measure the effectiveness of video-assisted learning regarding mental health education during the Pandemic among young adults. Methods: Video regarding mental health during the COVID-19 Pandemic was given to 35 young adults (18-25 years old) in Surabaya City using the zoom application. The pre-test and post-test consist of 10 questions and given before and after the video. The data was further analyzed descriptively and analytically using GARPH PRISM 5.00. Result: Increasing knowledge after video-assisted learning was observed, as there was an increasing number of respondents who had good knowledge regarding mental health during the COVID-19 Pandemic, from 22.9% to 45.7%. The data were further analyzed using a paired t-test to find the mean difference between the pre-test and post-test knowledge scores, both mean±SD (64.28±14.80 and 73.42±19.70, p<0.001, respectively). The effect of respondents’ backgrounds on the score was analyzed using a two-way ANOVA test. There was a significant difference between knowledge and their field of study (p<0.05), but not for the age, sex, and visiting online supporting group website. Conclusion: The video-assisted education effectively increased knowledge regarding mental health during the COVID-19 Pandemic among young adults in Surabaya. However, broader respondents are necessary before large implementation in the community.